A 60GHz VCO with 25.8% tuning range by switching return-path in 65nm CMOS - Fei, Wei (2013)
This paper presents a novel inductive tuning method for 60GHz voltage controlled oscillator (VCO) design. A new inductor-loaded transformer is proposed by configuring different current return-paths in the secondary coil of a transformer. Different from published inductive tuning methods, the proposed topology can achieve a multi-band, wide tuning range within compact area using only one transformer. A 60GHz VCO is implemented at 65nm CMOS process for demonstration. The obtained oscillation frequency can vary from 51.9GHz to 67.3GHz, which covers the full 60GHz band and provides a wide frequency tuning range of 25.8%.